Respon Masyarakat Desa Batu Cermin Dalam Pengembangan Daya Tarik Wisata Gua Batu Cermin, Labuan Bajo - Andriano Calrinto Mami; I Gusti Agung Oka Mahagangga (JURNAL DESTINASI PARIWISATA, 2020)
The tourist attraction of Batu Cermin Cave is a tourist attraction located in the city center of Labuan Bajo. Attractions offered to tourists who end up in Batu Cermin Cave in the form of natural attractions along the Cave where there are Wisatawaan Stalagtics and Stalagmites who visit Batu Cermin Cave are dominated by tourists from the archipelago. For now the management of Batu Cermin Cave tourist attraction is still managed by the local government in this case is the West Manggarai District Tourism and Culture Service. Later the management of Batu Cermin Cave will involve the Batu Cermin village so that in this study we will discuss "The Response of Batu Cermin Village Community in the Development of Tourism Attractions in Batu Cermin Cave, Labuan Bajo". The research method used in this study is a qualitative research method with qualitative descriptive data analysis techniques to explain the public response in the development of tourism in the tourist attraction of Batu Cermin Cave. The data source consists of primary data and secondary data. Data collection techniques using the method of observation, interviews and literature study. The determination of informants in this study used the Snowball technique. The results obtained are the existing conditions of Batu Cermin Cave tourist attraction in the stages of involvement in Butler's theory and the response of the community of Batu Cermin village is still in the Aphaty phase in the Irridex theory Keyword: Tourist Attraction, Batu Cermin Cave, Development of Tourism, Community Response, Travelers